2008
DOI: 10.1007/s11248-008-9174-7
|View full text |Cite
|
Sign up to set email alerts
|

RNA-interference in rice against Rice tungro bacilliform virus results in its decreased accumulation in inoculated rice plants

Abstract: Rice tungro is a viral disease seriously affecting rice production in South and Southeast Asia. Tungro is caused by the simultaneous infection in rice of Rice tungro bacilliform virus (RTBV), a double-stranded DNA virus and Rice tungro spherical virus (RTSV), a single-stranded RNA virus. To apply the concept of RNA-interference (RNAi) for the control of RTBV infection, transgenic rice plants expressing DNA encoding ORF IV of RTBV, both in sense as well as in anti-sense orientation, resulting in the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 35 publications
(30 reference statements)
1
41
0
1
Order By: Relevance
“…Disease-tolerant cultivars have thus far been selected by plant breeders; many such lines rely on resistance to insect transmission (5). Pathogen-derived resistance against RTD was reported as being only partially effective, although recent reports involving an RNAi construct are encouraging (5,9). Nevertheless, because of the limitations of current breeding programs and disease management, RTD remains a serious threat to rice production in regions of South and Southeast Asia.…”
mentioning
confidence: 99%
“…Disease-tolerant cultivars have thus far been selected by plant breeders; many such lines rely on resistance to insect transmission (5). Pathogen-derived resistance against RTD was reported as being only partially effective, although recent reports involving an RNAi construct are encouraging (5,9). Nevertheless, because of the limitations of current breeding programs and disease management, RTD remains a serious threat to rice production in regions of South and Southeast Asia.…”
mentioning
confidence: 99%
“…For example, resistance can be expressed at the penetration stage by determining the ability of a fungal pathogen to assimilate enough nutrients to be able to proliferate in the tissues or sporulate or spread. Host resistance can be constitutive or induced, and it has been demonstrated in several plant species that induced resistance can be regulated by different signalling pathways (Tyagi et al 2008). The present study shows that host resistance expression (in terms of disease severity) is also impacted by interactive effects of salinity, at least for common bean.…”
Section: Discussionmentioning
confidence: 99%
“…There are many other transgenic plants with enhanced defence by RNAi-mediated gene silencing, such as Tomato Yellow Leaf Curl Virus (TYLC)-resistant tomato (Fuentes et al 2006), Rice Tungro Bacilliform Virus (RTBV)-resistant rice (Tyagi et al 2008) and Citrus Tristeza Virus (CTV)-resistant mexican lime (López et al 2010). Schwind et al (2009) have even shown that using hpRNA construct in Solanum lycopersicum (tomato) against Potato Spindle Tuber Viroid (PSTVd) produce PSTVd-resistant tomato plant varieties.…”
Section: Virus Resistancementioning
confidence: 99%